THE CONCEPT MAPS AS A TOOL TO EVALUATE HOW TO PRESENT CONCEPTS IN TEXTBOOKS - Ahmadi, F.; Amini, A. (PEOPLE: International Journal of Social Sciences, 2015)
Textbooks should be designed in such a way that students achieve the discovery of relationships between concepts. In fact, when preparing learning materials, educational experts must prepare the conditions in such a way that at least pursuing students are able to achieve meaningful learning goals in this paper, we intend to investigate the method of writing a textbook by depicting conceptual maps. It seems that if we can depict a concept map by observing the method of arrangement and commitment tothe kind of relationships that are intended for students within the context of textbooks, we could access the knowledge organization of authors of the book in the desired topic. We believe that concept maps can be used as a tool to evaluate how to present concepts in textbooks. In this article, in addition to training steps of depicting a standard concept map, we specifically attempt to evaluate the writing style of content of textbooks in our country on the topic of basic electrostatic by conceptual maps.